Monitoring of Water Area Changes in Dongping County Based on Remote Sensing and Geographic Information System Technology - Xie, Yujiao (International Journal of Natural Resources and Environmental Studies, 2025)
With the development of modern industrialization, the problems of flood disaster, water quality and river channel change in the Yellow River Basin are prominent, and its water area is of great significance to water resource management, flood control safety and ecological environment protection. As an important part of the flood control system in the lower reaches of the Yellow River Basin, the water body of Dongping County is responsible for the dual tasks of dividing the Yellow River flood and regulating the flood of Wenhe River. Its water body area is constantly changing, which affects the water ecosystem, water quality and climate regulation in multiple dimensions. This study focuses on the monitoring of water body area in Dongping County. Landsat8 images from 2019-2023 are taken as the research object, and their preprocessing, classification by remote sensing supervision and decision tree classification are conducted. The resulting data are analyzed by accuracy verification and comparison. The results showed that the water body area of Dongping County increased year by year, from 2019 to 2023, the area increased by 8.08km². The change rate and increase rate of water body area in this region have a significant increasing trend. There was a significant positive correlation between precipitation and water area change in Dongping County, and the correlation coefficient was 0.931. It will help improve the water storage and flood control capacity of Dongping Lake, and play a positive role in reducing the risk of natural disasters and protecting the ecological environment.